PENCIPTAAN KEPERCAYAAN BERSAMA MELALUI ORGANISASI KOPERASI DAN INOVASI - Niniek F. Lantara (AkMen JURNAL ILMIAH, 2008)
If there is effort body which is full of controversy, possible that's co-operation. This matter because of that not rarely co-operation made as a means of to get the masked facility of social mission and have to be advocated. making co-operation peculiarly draw is fact that a lot of among co-operation develop; builded not even pursuant to belief capital, but also especial form of its organization device of vital importance in creating trustworthy relation. virtual Indonesia Co-Operation movement have to see the co-operation movement in world. In some world, co-operation have had the organization of world, having regular congress, having delegation in area and may sit on the world body as observer. its aspiration is sent widely